Analisis Perkembangan Kinerja Keuangan dengan Menggunakan Metode Du Pont System pada PT. Mustika Ratu Yang Go Publik di BEI - Riani Riani; Mifta Buheli; Indira Pratiwi Mustapa (Journal of Technopreneurship on Economics and Business Review, 2022)
This study aims to determine the financial performance of PT. Mustika Ratu Tbk, based on the 2012–2016 financial statements. The analytical method used in this study is the Du Pont System analysis method to assess the company's financial performance based on ATO, NPM, ROI, EM and ROE variables. The type of data used is secondary data, and the data source in this study is the financial reports issued by the Indonesia Stock Exchange. The population in this study is the company PT. Mustika Ratu Tbk. This research took five years, from 2012–2016, at PT. Mustika Ratu Tbk, which is listed on the Indonesia Stock Exchange. The research findings show that based on the overall financial performance of the three issuers, it generally fluctuates, so it can be said that the company's financial performance is that of PT. Mustika Ratu Tbk, which is not in good condition.